Rapid Molecular Microbiologic Diagnosis of Prosthetic Joint Infection - Cazanave, Charles (American Society for Microbiology, 2013)
We previously showed that culture of samples obtained by prosthesis vortexing and sonication was more sensitive than tissue culture for prosthetic joint infection (PJI) diagnosis. Despite improved sensitivity, culture-negative cases remained; furthermore, culture has a long turnaround time. We designed a genus-/group-specific rapid PCR assay panel targeting PJI bacteria and applied it to samples obtained by vortexing and sonicating explanted hip and knee prostheses, and we compared the results to those with sonicate fluid and periprosthetic tissue culture obtained at revision or resection arthroplasty. We studied 434 subjects with knee (n = 272) or hip (n = 162) prostheses; using a standardized definition, 144 had PJI. Sensitivities of tissue culture, of sonicate fluid culture, and of PCR were 70.1, 72.9, and 77.1%, respectively. Specificities were 97.9, 98.3, and 97.9%, respectively. Sonicate fluid PCR was more sensitive than tissue culture (P = 0.04). PCR of prosthesis sonication samples is more sensitive than tissue culture for the microbiologic diagnosis of prosthetic hip and knee infection and provides same-day PJI diagnosis with definition of microbiology. The high assay specificity suggests that typical PJI bacteria may not cause aseptic implant failure.